Potential associations of selected polymorphic genetic variants with COVID-19 disease susceptibility and severity - Orsolya Mózner; Edit Szabó; Anna Kulin; György Várady; Judit Moldvay; Vivien Vass; Andrea Szentesi; Ágoston Jánosi; Péter Hegyi; Balázs Sarkadi (PLoS ONE, 2025)
In this study, we analyzed the potential associations of selected laboratory and anamnestic parameters, as well as 12 genetic polymorphisms (SNPs), with clinical COVID-19 occurrence and severity in 869 hospitalized patients. The SNPs analyzed by qPCR were selected based on population-wide genetic (GWAS) data previously indicating association with the severity of COVID-19, and additional SNPs that have been shown to be important in cellular processes were also examined. We confirmed the associations of COVID-19 with pre-existing diabetes and found an unexpected association between less severe disease and the loss of smell and taste. Regarding the genetic polymorphisms, a higher allele frequency of the LZTFL1 and IFNAR2 minor variants significantly correlated with greater COVID-19 disease susceptibility (hospitalization) and severity, and a similar tendency was observed for the RAVER1 and the MUC5B variants. Interestingly, the ATP2B4 minor haplotype, protecting against malaria, correlated with an increased disease susceptibility, while in diabetic patients disease susceptibility was lower in the presence of a reduced-function ABCG2 transporter variant. Our current results, which should be reinforced by larger studies, indicate that together with laboratory and anamnestic parameters, genetic polymorphisms may have predictive value for the clinical occurrence and severity of COVID-19.